Virtual Acoustics - Michael VORLÄNDER (Archives of Acoustics)
Virtual Reality (VR) systems are used in engineering, architecture, design and in applications of biomedical research. The component of acoustics in such VR systems enables the creation of audio-visual stimuli for applications in room acoustics, building acoustics, automotive acoustics, environmental noise control, machinery noise control, and hearing research. The basis is an appropriate acoustic simulation and auralization technique together with signal processing tools. Auralization is based on time-domain modelling of the components of sound source characterization, sound propagation, and on spatial audio technology. Whether the virtual environment is considered sufficiently accurate or not, depends on many perceptual factors, and on the pre-conditioning and immersion of the user in the virtual environment. In this presentation the processing steps for creation of Virtual Acoustic Environments and the achievable degree of realism are briefly reviewed. Applications are discussed in examples of room acoustics, archeological acoustics, aircraft noise, and audiology.